2024
DOI: 10.1001/jama.2023.27022
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bivalent mRNA COVID-19 Vaccines in Preventing SARS-CoV-2 Infection in Children and Adolescents Aged 5 to 17 Years

Leora R. Feldstein,
Amadea Britton,
Lauren Grant
et al.

Abstract: ImportanceBivalent mRNA COVID-19 vaccines were recommended in the US for children and adolescents aged 12 years or older on September 1, 2022, and for children aged 5 to 11 years on October 12, 2022; however, data demonstrating the effectiveness of bivalent COVID-19 vaccines are limited.ObjectiveTo assess the effectiveness of bivalent COVID-19 vaccines against SARS-CoV-2 infection and symptomatic COVID-19 among children and adolescents.Design, Setting, and ParticipantsData for the period September 4, 2022, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In a separate U.S. study of children and adolescents aged 5–15 years, VE against symptomatic SARS-CoV-2 infections was reported to wane in the months after a second dose, with improved VE observed after receipt of a booster dose ( 4 ). Effectiveness of bivalent vaccine formulations against pediatric hospitalizations was not estimable in this investigation; however, two recent studies report that receipt of a bivalent vaccine was associated with higher VE against symptomatic pediatric infections ( 6 ) and COVID-19–related hospitalizations in immunocompetent adults ( 7 ).…”
Section: Discussionmentioning
confidence: 71%
“…In a separate U.S. study of children and adolescents aged 5–15 years, VE against symptomatic SARS-CoV-2 infections was reported to wane in the months after a second dose, with improved VE observed after receipt of a booster dose ( 4 ). Effectiveness of bivalent vaccine formulations against pediatric hospitalizations was not estimable in this investigation; however, two recent studies report that receipt of a bivalent vaccine was associated with higher VE against symptomatic pediatric infections ( 6 ) and COVID-19–related hospitalizations in immunocompetent adults ( 7 ).…”
Section: Discussionmentioning
confidence: 71%
“…Of the 426 infections discovered, 56.8% were asymptomatic, and symptomatic infections were mainly reported among those either not vaccinated, or who had only received the original monovalent vaccine. 22 Recent research 23 has also shown that viral load rises later, on average, during Omicron infections compared with earlier in the pandemic where the highest viral load in throat swabs was reported at the time of symptom onset, and the inferred infectiousness peaked on or before symptom onset. 24 The viral load in Omicron infections was found to most commonly peak on the third or fourth day after symptoms developed.…”
Section: The End Of Population-wide Transmission Control Measuresmentioning
confidence: 99%